Church history in plain language - SHELLY, Bruce L. (Dallas : Word Publishing, 1995)
"Brings the story of Christianity into the twenty-first century. This latest edition of the book takes a close look at the rapid growth of evangelical and Pentecostal Christianity in the southern hemisphere, addresses the decline in traditional mainline denominations, examines the influence of technology on the spread of the gospel, and discusses how Christianity intersects with other religions in countries all over the world."--Publisher description.
Includes bibliography and index
Keywords: Church history, Christianity History